Pengembangan Perangkat Pembelajaran Matematika Realistik di Sekolah Menengah Pertama - Mulbar, Usman (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD FILEThe aim of the research was to produce a good quality of realistic mathematics instructional package at the Junior High School in Makassar. This study was a qualitative research which preceded by developing a realistic mathematics instructional package (PMR Package). The development of the PMR package was employed based on instructional system which developed by Thiagarajanâ€™s et al. (1974). The development phases which took place were: (1) defining phase, (2) designing phase, and (3) developing phase. Â Key words: Development, mathematics education, realistic